Bright Room‐Temperature Single‐Photon Emission from Defects in Gallium Nitride. Issue 12 (9th February 2017) - Berhane, Amanuel M.; Jeong, Kwang‐Yong; Bodrog, Zoltán; Fiedler, Saskia; Schröder, Tim; Triviño, Noelia Vico; Palacios, Tomás; Gali, Adam; Toth, Milos; Englund, Dirk; Aharonovich, Igor
Abstract : Room‐temperature quantum emitters in gallium nitride (GaN) are reported. The emitters originate from cubic inclusions in hexagonal lattice and exhibit narrowband luminescence in the red spectral range. The sources are found in different GaN substrates, and therefore are promising for scalable quantum technologies.